A new synopsis of the mosquitoes (Diptera: Culicidae) of Colorado - Rose, Dominic Anthony, author; Kondratieff, Boris, advisor; Weissmann, Michael, advisor; Savage, Harry, committee member; Foy, Brian, committee member (Colorado State University. Libraries, 2016)
Harmston and Lawson (1967) provided the most recent comprehensive review of the mosquitoes of Colorado, reporting 42 species in six genera. Over the last 48 years, a number of important studies that included mosquitoes of Colorado have been completed enhancing the knowledge of this medically important group of flies. To date, the number of Colorado mosquitoes has increased to 54 species in seven genera. Additionally, mosquito vectored pathogens of humans and animals have shifted in Colorado from primarily Western equine encephalitis virus and St. Louis encephalitis virus to primarily West Nile virus. The objective of the current project is to provide an up-to-date synopsis of the species and genera known to occur in Colorado including distributions at a county scale. The study also provides up-to-date illustrated keys to the adult females, fourth instar larvae, and a summary of the important taxonomic characteristics that allow separation of species for both adult females and fourth instar larvae. The species summary includes relevant biological notes and comments on each species such as its phenology, overwintering stage, larval habitat, host preference, medical importance and unique behaviors.
Keywords: medical importance; public health; taxonomy; mosquitoes; Culicidae